Presentation is loading. Please wait.

Presentation is loading. Please wait.

Chapter 6 Section 4.

Similar presentations


Presentation on theme: "Chapter 6 Section 4."— Presentation transcript:

1 Chapter 6 Section 4

2 A General Approach to Factoring
6.4 A General Approach to Factoring Factor out any common factor. Factor binomials. Factor trinomials. Factor polynomials of more than three terms.

3 Factoring a Polynomial
A General Approach to Factoring Factoring a Polynomial Step 1 Factor out any common factor. Step 2 If the polynomial is a binomial, check to see if it is the difference of squares, a difference of cubes, or a sum of cubes. If the polynomial is a trinomial, check to see if it is a perfect square trinomial. If it is not, factor as in Section 6.2. If the polynomial has more than three terms, try to factor by grouping. Step 3 Check the factored form by multiplying. Slide

4 Factor out any common factor.
Objective 1 Factor out any common factor. Slide

5 Factoring Out a Common Factor
CLASSROOM EXAMPLE 1 Factoring Out a Common Factor Factor each polynomial. 2x3 + 10x2 – 4x The GCF is 2x. = 2x(x2 + 5x – 2) 12m(p – q) – 7n(p – q) The GCF is (p – q) = (p – q)(12m – 7n) Solution: Slide

6 Objective 2 Factor binomials. Slide

7 Factor binomials. Factoring a Binomial
For a binomial (two terms), check for the following: Difference of Squares: x2 – y2 = (x – y)(x + y) Difference of Cubes: x3 – y3 = (x – y)(x2 + xy + y2) Sum of Cubes: x3 + y3 = (x + y)(x2 – xy + y2) Slide

8 Factor each binomial, if possible. 36x2 – y2 Difference of squares
CLASSROOM EXAMPLE 2 Factoring Binomials Factor each binomial, if possible. 36x2 – y2 Difference of squares = (6x)2 – (y)2 = (6x – y)(6x + y) 4t2 + 1 The binomial is prime. It is the sum of squares. 125x3 – 27y3 = = (5x – 3y)[(5x)2 + (5x)(3y) + (3y)2] = (5x – 3y)(25x2 + 15xy + 9y2) Solution: Slide

9 Objective 3 Factor trinomials. Slide

10 Factor trinomials. Factoring a Trinomial
For a trinomial (three terms), decide whether it is a perfect square trinomial of either of these forms x2 + 2xy + y2 = (x + y)2 or x2 – 2xy + y2 = (x – y)2 If not, use the methods of Section 6.2. Slide

11 Perfect square trinomial
CLASSROOM EXAMPLE 3 Factoring Trinomials Factor each trinomial. 16m2 + 56m + 49 = (4m + 7)2 8t2 – 13t + 5 Two integer factors whose sum is 8(5) = 40 and whose sum is –13 are –5 and –8. = 8t2 – 5t – 8t + 5 = t(8t – 5) – 1(8t – 5) = (8t – 5)(t – 1) Solution: Perfect square trinomial Slide

12 Factoring Trinomials (cont’d)
CLASSROOM EXAMPLE 3 Factoring Trinomials (cont’d) Factor the trinomial. 6x2 – 3x – 63 Factor out the GCF of 3. = 3(2x2 – x – 21) Two factors whose product is 2(–21) = – 42 and whose sum is –1 are –7 and 6. = 3[2x2 – 7x + 6x – 21] = 3[x(2x – 7) + 3(2x – 7)] = 3(2x – 7)(x + 3) Solution: Slide

13 Factor polynomials of more than three terms.
Objective 3 Factor polynomials of more than three terms. Slide

14 Factoring Polynomials with More than Three Terms
CLASSROOM EXAMPLE 4 Factoring Polynomials with More than Three Terms Factor each polynomial. p3 – 2pq2 + p2q – 2q3 = (p3 – 2pq2) +(p2q – 2q3) = p(p2 – 2q2) + q(p2 – 2q2) = (p2 – 2q2)(p + q) 9x2 + 24x + 16 – y2 = (9x2 + 24x + 16) – y2 = (3x + 4)2 – y2 = [(3x + 4) + y)][(3x + 4) – y)] = (3x y)(3x + 4 – y) Solution: Slide

15 = {(4a + b)[(4a)2 – 4ab + b2]} + [(4a + b)(4a – b)]
CLASSROOM EXAMPLE 4 Factoring Polynomials with More than Three Terms (cont’d) Factor the polynomial. 64a3 + 16a2 + b3 – b2 = (64a3 + b3) + (16a2 – b2) = [(4a)3 + b3] + [(4a)2 – b2] = {(4a + b)[(4a)2 – 4ab + b2]} + [(4a + b)(4a – b)] = [(4a + b)(16a2 – 4ab + b2)] + [(4a + b)(4a – b)] = (4a + b)(16a2 – 4ab + b2 + 4a – b) Solution: Slide


Download ppt "Chapter 6 Section 4."

Similar presentations


Ads by Google